1994
DOI: 10.1002/jcp.1041610209
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and differentiation of rat adipose precursor cells in chemically defined medium: Differential action of anti‐adipogenic agents

Abstract: Primary rat adipose precursor cells, maintained in the minimal chemically defined medium (ITT medium) able to promote differentiation, have been used to investigate the ability of several agents to modulate their proliferation and their differentiation. Fetuin and fibroblast growth factor (FGF), which exhibited a strong and a weak mitogenic activity, respectively, do not significantly affect the proportion of differentiated cells as indicated by glycerol-3-phosphate dehydrogenase (GPDH) activity values. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 32 publications
3
43
0
1
Order By: Relevance
“…Similar results were reported for rat, porcine and human primary preadipocytes [179,185,186,247]. As suggested for PDGF and FGF, this negative effect appears to be independent on a proliferative action [185,240].…”
Section: Other Growth Factors and Cytokinessupporting
confidence: 86%
See 4 more Smart Citations
“…Similar results were reported for rat, porcine and human primary preadipocytes [179,185,186,247]. As suggested for PDGF and FGF, this negative effect appears to be independent on a proliferative action [185,240].…”
Section: Other Growth Factors and Cytokinessupporting
confidence: 86%
“…Studies on 3T3-L1 cells revealed that EGF increases adipose conversion in serum-free medium [15] whereas negative effect were obtained in serum-containing medium [3]. Furthermore, EGF increases the differentiation of porcine preadipocytes [27], whereas it inhibits the adipose conversion of rodent and human preadipose cells cultured in similar conditions [107,198,247]. Transforming growth factor α, that can be expressed by preadipose cells, exhibits antiadipogenic activities when tested on 3T3-F442A and rat preadipose cells [154,198,199].…”
Section: Other Growth Factors and Cytokinesmentioning
confidence: 99%
See 3 more Smart Citations